The Influence of Floating Net Cages on Trophic state Levels around Dam Site Koto Panjang ReservoirKampar Regency, Riau Province - Sitohang, Dohar; Dahril, Tengku; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTFish cultivation activities in floating net cages produce uneaten feed and metabolic wastes. This study aims to know to know the effect of floating net cages (KJA) on the level of trophic state of the waters around the Dam Site of Koto Panjang Reservoir.Sampling was carried out at three stations, namely station 1 (less KJA), station 2 (moderate KJA), and station 3 (full KJA). Sampling was done 3 times once/week. Water quality parameters measured are temperature, transparency, pH, dissolved oxygen, CO2,total P, chlorophyll-a, and nitrate.The results shown that the average concentration of Total P : 0.27 to 0.33 mg/L, chlorophyll-a concentrations ranged : 2.76 to 16.31 µ/L, and transparency  ranged : 99-123 cm. temperature : 29-32.33 ° C, pH : 5-6, dissolved oxygen : 4.47-6.99 mg/L, CO25.32-15.98 mg/L, and nitrate concentration : 0.04-0.08 mg/L.The floating net cages have affected the concentration of Total P, chlorophyll-a, and nitrate. The two way ANOVA statistical test on the concentration of Total P, chlorophyll-a, and nitrate was not significantly different between stations and over time. TSI (State Trophic Index) value: 63.08-68.69. Based on TSI value,  the waters around Dam Site of  Koto Panjang Reservoir can be categorized as moderate  to eutrophic.Keywords: TSI (StateTrophic Index), Floating net cage, Water Quality,  PLTA Koto Panjang  Reservoir, Eutrophic.